2004
DOI: 10.1172/jci19478
|View full text |Cite
|
Sign up to set email alerts
|

Increased ocular levels of IGF-1 in transgenic mice lead to diabetes-like eye disease

Abstract: IGF-1 has been associated with the pathogenesis of diabetic retinopathy, although its role is not fully understood. Here we show that normoglycemic/normoinsulinemic transgenic mice overexpressing IGF-1 in the retina developed most alterations seen in human diabetic eye disease. A paracrine effect of IGF-1 in the retina initiated vascular alterations that progressed from nonproliferative to proliferative retinopathy and retinal detachment. Eyes from 2-month-old transgenic mice showed loss of pericytes and thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 57 publications
5
116
1
4
Order By: Relevance
“…Our observations showing decreased levels of Foxf1 and Foxf2 mRNA in Lif, Igf-I, and Lif/Igf-I knockouts would support alterations in mesenchymal and vasculogenesis maturation mediated by IGF-I and LIF. Although LIF function in vasculogenesis is poorly known, these results are consistent with previous reports linking IGF-I and angiogenesis in tissues such as brain and retina (Hellstrom et al, 2001;LopezLopez et al, 2004;Ruberte et al, 2004). Blocking IGF-IR signalling in lung explants, in addition to reduced lung growth and branching of the epithelium, resulted in an inhibition of endothelial cell development (Han et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Our observations showing decreased levels of Foxf1 and Foxf2 mRNA in Lif, Igf-I, and Lif/Igf-I knockouts would support alterations in mesenchymal and vasculogenesis maturation mediated by IGF-I and LIF. Although LIF function in vasculogenesis is poorly known, these results are consistent with previous reports linking IGF-I and angiogenesis in tissues such as brain and retina (Hellstrom et al, 2001;LopezLopez et al, 2004;Ruberte et al, 2004). Blocking IGF-IR signalling in lung explants, in addition to reduced lung growth and branching of the epithelium, resulted in an inhibition of endothelial cell development (Han et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Glucose levels did not differ significantly between wt and trVEGF029 (wt: 5.36±0.99 mmol/l; trVEGF029: 5.42± 0.90 mmol/l; p>0.05) and were similar to those in the aqueous humour of an IGF-1 transgenic mouse [30].…”
Section: Retinal Trypsin Digestion For Quantification Of Endothelial mentioning
confidence: 71%
“…Early studies suggested that GH-deficient patients with diabetes were protected from retinopathy, and pituitary ablation, which decreases GH levels, was a treatment for severe retinopathy before the advent of laser photocoagulation. Overexpression of IGF1 in the retina resulted in changes similar to those of diabetic retinopathy (Ruberte et al 2004). Subsequently, intraocular overexpression of IGF1 has been shown to result in breakdown of the blood-retinal barrier and increased retinal vascular permeability (Haurigot et al 2009).…”
Section: Diabetic Retinopathymentioning
confidence: 98%